2022
DOI: 10.1155/2022/7599098
|View full text |Cite
|
Sign up to set email alerts
|

RIPK4 Is an Immune Regulating-Associated Biomarker for Ovarian Cancer and Possesses Generalization Value in Pan-Cancer

Abstract: Ovarian cancer (OC) is the most lethal gynecologic cancer. Many studies have reported that RIPK4 (receptor interacting serine/threonine kinase 4) displayed a dysregulated level in many types of tumors. However, its expressions and functions in OC were rarely reported. The levels of RIPK4 were detected in OC and nontumor specimens using TCGA and GEO datasets. The prognostic values of RIPK4 in patients were determined using Kaplan-Meier methods and Kaplan-Meier assays. GO assays and KEGG pathway assays were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Given that RIPK4 has been shown to play a role in the activation of the NF-κB pathway, and its expression negatively correlates with the predicted presence of T cells in human ovarian cancer [ 22 , 33 ], we reasoned that RIPK4 may be modulating the tumor microenvironment. To comprehensively assess how RIPK4 shapes the immune landscape of TNBC, we performed spectral flow cytometry on our experimental lung metastasis assay using a 19-plex antibody panel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that RIPK4 has been shown to play a role in the activation of the NF-κB pathway, and its expression negatively correlates with the predicted presence of T cells in human ovarian cancer [ 22 , 33 ], we reasoned that RIPK4 may be modulating the tumor microenvironment. To comprehensively assess how RIPK4 shapes the immune landscape of TNBC, we performed spectral flow cytometry on our experimental lung metastasis assay using a 19-plex antibody panel.…”
Section: Resultsmentioning
confidence: 99%
“…Given that RIPK4 has been shown to play a role in the activation of the NF-κB pathway, and its expression negatively correlates with the predicted presence of T cells in human ovarian cancer [22,33], we reasoned that RIPK4 may be modulating the tumor microenvironment.…”
Section: The Tumor Immune Landscape Of Metastatic Lesions Is Modulate...mentioning
confidence: 99%
“…Receptor-interacting protein kinase (RIPK) family genes have been found to be of significant importance to the innate immune system, as they play a role in modulating the progression of immunerelated diseases and tumors [5][6][7][8][9][10][11]. Dysregulation of the innate immune system can lead to immunodeficiency or autoinflammatory diseases.…”
Section: Ivyspringmentioning
confidence: 99%
“…The upregulation of RIPK3 has been shown to increase the production of immunostimulatory cytokines in the tumor microenvironment, leading to a robust cytotoxic anti-tumor immune response 9 . Additionally, RIPK4 has been identified as an immune regulating-associated biomarker in ovarian cancer 11 , 29 , where it plays a role in regulating the growth of squamous cell carcinoma 30 and cell-cell adhesion in epidermal development and homeostasis 31 . All of the aforementioned studies have demonstrated the significant role of RIPKs genes in the regulation of immune-related diseases, such as tumors.…”
Section: Introductionmentioning
confidence: 99%